Sowing the Gospel in the southern "Vorstenlanden"; Wonogiri in the Protestant evangelists’ travelogues in the early twentieth century - Wardhana, Adi Putra Surya; Pradita, Dennys (Wacana, Journal of the Humanities of Indonesia, 2024)
The goal of this study is to analyse the travelogues of Protestant evangelists in Wonogiri, a topic so far barely touched upon. Despite being a predominantly Muslim community, Wonogiri was one of the areas in the principalities of Surakarta targeted by the zending. Therefore, this study explores various aspects, including the purpose behind the visits of Protestant missionaries, the discourses presented in the travelogues, and the perspectives of these evangelists on the belief system prevalent in the community in the early twentieth century. Based on several travel accounts, this research utilizes a critical discourse analysis approach. The evangelists built a discourse which intertwined Christianity and identity discourse. The narratives reveal stark differences between the abangan communities and the stricter Muslims identified as putihan. The indigenous people who embraced Protestantism were perceived as the chosen ones, while those who remained unconverted were considered as the others. This reality highlights the inherent European-Christian perspective adopted by the travelogue writers.